Leisure boat tourism: residents’ attitudes towards nautical tourism development - Gon, M.; Osti, L.; Pechlaner, Harald (Emerald Group Publishing Limited, 2016)
Purpose: This paper aims to analyse how leisure boat tourism impacts are perceived by local communities in coastal areas. For this purpose, a review of the literature on nautical and leisure boat tourism, together with residents’ attitudes, is presented. On that basis, authors consider economic, socio-cultural and environmental impacts, together with general development and future policies of nautical tourism, and cluster the coastal community according to their attitudes towards leisure boat tourism. Design/methodology/approach: Primary data are collected among residents of coastal municipalities in the north part of the Adriatic Sea. Within the theoretical framework of social representation, a cluster analysis is performed on 233 valid questionnaires, collected during winter 2013. Findings: Interviewed residents believe that leisure boating has a long tradition and has offered improvements to the municipalities as tourism destinations. They consider leisure boat tourism as a catalyst for tourism development and international tourists’ attraction. The cluster analysis reveals the existence of three homogeneous groups of residents labelled as supporters (51 per cent), cautious (29 per cent) and sceptics (20 per cent). Practical implications: Practical implications are derived for destination managers and destination management organizations (DMOs) in addressing internal marketing and larger advertisement of the positive impacts leisure boat tourism has over the local community. Originality/value: The paper enriches the discussion on residents’ perceptions on nautical tourism and specifically on leisure boat tourism in coastal areas. Limitations are linked to the exploratory nature of the research paper, the sample and the geographical connotation of the study area. Further research will enlarge the data collection to a wider number of coastal communities and integrate results with qualitative analysis.